[18F]FDG PET/CT performs better than CT in determining the bone biopsy site : randomized controlled clinical trial - Yujie Chang; Yifeng Gu; Shunyi Ruan; Shengyu Xu; Jing Sun; Zhiyuan Jiang; Guangyu Yao; Zhiyu Wang; Hui Zhao (Cancer Imaging)
Abstract Background Bone biopsy is the gold standard for diagnosing bone metastases. However, there is no clinical consensus regarding the optimal imaging test for determining the puncture site. Methods We compared the performance of [18F]FDG PET/CT with CT in detecting bone metastases to achieve the highest biopsy efficiency. This registered prospective study enrolled 273 patients with bone lesions who were treated between January 2020 and March 2021. Patients were randomly assigned to undergo [18F]FDG PET/CT or CT to determine the puncture site before bone biopsy. The accuracy, sensitivity, specificity, second biopsy rate, diagnostic time and cost-effectiveness of the two imaging tests were compared. Results The accuracy and sensitivity of [18F]FDG PET/CT group in detecting bone metastases were significantly higher than CT group(97.08% vs. 90.44%, 98.76% vs. 92.22%, P < 0.05). The second biopsy rate was significantly lower in the [18F]FDG PET/CT group (2.19% vs. 5.15%; P < 0.05). The diagnostic time of [18F]FDG PET/CT was 18.33 ± 2.08 days, which was significantly shorter than 21.28 ± 1.25 days in CT group ( P < 0.05). The cost of [18F] FDG PETCT is 11428.35 yuan, and the cost of CT is 13287.52 yuan; the incremental cost is 1859.17 yuan. SUVmax > 6.3 combined with ALP > 103 U/L showed a tendency for tumor metastases with an AUC of 0.901 (95%CI 0.839 to 0.946, P < 0.001). Conclusion [18F]FDG PET/CT has better performance and cost-effectiveness than CT in determining the bone biopsy site for suspect bone metastases. Trial registration The prospective study was registered on 2018-04-10, and the registration number is ChiCTR1800015540.